White lupin: An alternative to pea in oat-legume forage mixtures grown in Newfoundland - McKenzie, D. B.; Spaner, D. (Canadian Journal of Plant Science, 1999)
"Peas-oats-vetch" is a traditional annual forage crop in Newfoundland, cut as needed in late fall, and fed as fresh feed. We tested the potential of increasing yield biomass and N concentration of the annual forage mixture through the substitution of white lupin (Lupinus albus L.) for pea (Pisum sativum L.) in 1990 and 1991. On mineral soils, lupin and pea were seeded at rates of 10, 20, 40, and 80 seeds m −2 in 132 seeds m −2 oat (Avena sativa L.) mixtures, and compared with pure-stand oat. Oat-lupin and oat-pea mixtures, planted at similar seeding rates, were also harvested at weekly intervals between 8 and 14 wk after planting. Oat-lupin, oat-pea and pure-stand oat were evaluated in an additional experiment on peat soils. On mineral soils, oat-lupin mixtures yielded forage with similar, or greater, dry matter yields and N concentration than pure-stand oats and oat-pea mixtures. Greatest yields were attained when mixtures were planted with 20 to 40 lupin seeds m −2 , and harvested 10 to 12 wk after early summer planting. On peat soils, white lupins were susceptible to diseases that did not affect peas, resulting in oat-lupin yields that did not differ from pure-stand oats. White lupin can be considered an alternative legume in oat-legume mixtures grown on mineral soils in eastern Newfoundland. Key words: Lupinus albus L., Pisum sativum L., oat-legume forage, podzolic soil, peat soil